Aphanius dispar, a larvivorous fish as biocontrol of malarial mosquito in Al-Hudaidah Province, Yemen - Fareed, Khalid H.; Baban, Mahdi R. (Philippines Rushing Water Publishers, 1995)
"The potential use of Aphanius dispar, a larvivorous fish for the control of malarial mosquito larvae in Al-Hudaidah Province, Yemen was examined. A total of 30 male and female individuals of A. dispar distributed in six classes according to length was used. Results of feeding experiements in controlled-pond conditions showed that A. dispar regardless of sex type, is an effective biocontrol of mosquito larvae."
Keywords: Mosquitoes; Malaria; Al-Hudaidah Province, Yemen; Larvivorous fish